MBernAca/MorphoECG: MorphoECG v1.0 - MBernAca (Zenodo, 2021)
This repository includes Matlab scripts used to perform morphological analyses on fjords in East Central Greenland (65°N-75°N). It is associated with the companion paper 'The impact of lithology on fjord morphology' by M. BERNARD (Rennes University), P. STEER (Rennes University), K. Gallagher (Rennes University) and D.L. Egholm(Aarhus University). The script 'Main.m' allows for the extraction of fjord widths and depths, with drainage area computed as a proxy for ice discharge. The code 'plot_results.m' computes the power-law fits for width or depth against drainage area, for each lithological domain. Authors: Maxime Bernard (Rennes University, France), Philippe Steer (Rennes University, France)